1985
DOI: 10.1113/jphysiol.1985.sp015833
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium ions inhibit exocytotic vasopressin release from the rat neurohypophysis.

Abstract: SUMMARY1. Single rat neurointermediate lobes (n.i.l.s) were fixed by their stalks to a platinum wire clip electrode and incubated in oxygenated Krebs-HEPES medium. Vasopressin release into the medium was determined by radioimmunoassay. Vasopressin secretion was increased by different stimuli and the effects of gadolinium (Gd3+) were tested.2. Electrical stimulation (15 Hz, three times 1 min with 1 min intervals) increased vasopressin release in a calcium-dependent manner. Gd3+ (10 ftM to 3 mM) inhibited the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
1
3
0
1
Order By: Relevance
“…The results support the view that Gd3+ blocks N-type Ca2 + channels (Docherty, 1988) and suggest that such channels are the major type involved in nerve-impulse evoked transmitter release from frog motor nerve terminals. These findings agree with previous studies showing that Gd3+ inhibits [3H]-noradrenaline and vasopressin release (Bourne & Trifaro, 1982;Muscholl et al, 1985) and effectively reduced depolarization-induced 45Ca2+ uptake into cultured chromaffin cells and rat brain synaptosomes (Nachshen, 1984).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results support the view that Gd3+ blocks N-type Ca2 + channels (Docherty, 1988) and suggest that such channels are the major type involved in nerve-impulse evoked transmitter release from frog motor nerve terminals. These findings agree with previous studies showing that Gd3+ inhibits [3H]-noradrenaline and vasopressin release (Bourne & Trifaro, 1982;Muscholl et al, 1985) and effectively reduced depolarization-induced 45Ca2+ uptake into cultured chromaffin cells and rat brain synaptosomes (Nachshen, 1984).…”
Section: Discussionsupporting
confidence: 93%
“…On isolated adrenal medullary cells and in the rat neurohypophysis no effect of Gd3+ was detected on the basal release of [3H]-noradrenaline and vasopressin (Bourne & Trifaro, 1982;Muscholl et al, 1985) while in striatal synaptosomal preparations Gd3 + slightly increased basal [3H]-dopamine release (Sheer, 1989). The increase in spontaneous quantal release caused by Gd3+ is most probably the result of its entry into motor nerve terminals and its intracellular action is reminiscent of the action of La3 + (Curtis et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Ogino et al (1994) suggested that zinc hydroxide, a colloidal form of zinc under neutral conditions, was taken up by rat neutrophils, and that it stimulated respiratory burst. Moreover, it is well known that gadolinium ions have various pharmacological actions (Dos Remedios & Barden 1977;Bourne & Trifaro 1982;Muscholl et al 1985;Yang & Sachs 1989;Bear & Li 1991). Based on these findings, we speculated that GdC13 may affect Kupffer cell function.…”
Section: Discussionmentioning
confidence: 77%
“…Edwards et al (1993) reported that GdC& inhibited CCLinduced liver injury via the inhibition of Kupffer cell functions. However, gadolinium ions have various pharmacological actions such as an inhibition of the polymerization of G-actin to form F-actin (Dos Remedios & Barden 1977), release of catecholamine from isolated adrenal medullary cells (Bourne & Trifaro 1982), and blocking of calcium channels (Bourne & Trifaro 1982;Muscholl et al 1985;Yang & Sachs 1989;Bear & Li 1991).…”
mentioning
confidence: 99%
“…Τα ιόντα των λανθανιδών μπορούν να προσδεθούν στην κυτταρική επιφάνεια καταστρέφοντας την σταθερότητα των μεμβρανών και αυξάνοντας την διαπερατότητα τους (Chang, 1991 (Ma et al, 1993). Ως συνέπεια των γεγονότων αυτών είναι η παύση των νευρικών ώσεων και η συστολή των λείων, σκελετικών και καρδιακών μυών, η λειτουργία του ενδοθηλίου των αγγείων και σταματούν τις διάφορες ορμονικές αποκρίσεις (Barry et al, 1978;Morris, 1980;Muscholl et al, 1985).…”
Section: χρήσεις και εφαρμογές των λανθανιδώνunclassified